Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

When Scientific Reassessment Fails Citizen Science. Comment on Soldo, A. When Citizen Science Becomes Speculation: Evaluating the Reliability of Lamnid Shark Identification from Photographic Records in the Mediterranean. J. Mar. Sci. Eng. 2026, 14, 173 - Patrick L. Jambura; Julia Türtscher; Joshua K. Moyer; Kenshu Shimada; Ilija Ćetković; Branko Dragičević; Pero Ugarković; Mišo Pavičić; Phillip C. Sternes; Simone Niedermüller; Jacopo Bernardi; Matteo Barbato; et al. (Journal of Marine Science and Engineering, 2026)
Soldo [...]

A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

A dataset of plant communities invaded by Acacia sp. pl. and Robinia pseudoacacia in Italy - Eugenia Siccardi; Alice Misuri; Alicia Teresa Rosario Acosta; Claudia Angiolini; Dario Azzaro; Gianluigi Bacchetta; Simonetta Bagella; Elena Barni; Giuseppe Bazan; Maria E. Boi; Gianmaria Bonari; Giuseppe Brundu; et al. (Plant Biosystems, 2026)
The full extent of the ecological threat posed by non-native invasive leguminous N-fixing trees to Italian ecosystems has not been thoroughly documented at the national level. This study, conducted by the Working Group on Alien Species of the Italian Botanical Society, aims to develop a comprehensive dataset that provides information on invaded and non-invaded areas, supporting multi-scale ecological analyses on the impact of black locust ( Robinia pseudoacacia ) and different Acacia sensu lato species across Italy. We conducted paired vegetation surveys across 18 distinct invasion contexts, comparing invaded and non-invaded plant communities. These invasion contexts were selected opportunistically by the participating research groups, based on the availability of well-documented sites where the focal species were already established and exerting ecologically relevant effects. Overall, we conducted 342 vegetation surveys across 10 Italian administrative regions and identified 824 plant species. Our surveys highlighted areas affected by five invasive species, including A. dealbata, A. mearnsii, A. saligna , Vachellia karroo , and R. pseudoacacia . Most of the surveys focused on areas invaded by A. saligna . The plant formations investigated fall under 23 EUNIS habitat codes and 10 Natura 2000 habitats. The most frequently occurring vegetation types under the EUNIS code are temperate and Mediterranean-montane scrub, and the most frequently investigated habitat is priority habitat 2250*: Coastal dunes with Juniperus sp. pl. This dataset provides a robust baseline that can facilitate more detailed assessments of the impacts of these invasive species on native ecosystems.

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

The rolling stones' legacy: Rhodoliths retain their habitat function after algal death - Fernanda C. de Oliveira-Carlos; Pedro Augusto dos Santos Longo; Jorge L. Gutiérrez; Cinthya Simone Gomes Santos; Andre R. Senna; Guilherme H. Pereira-Filho (Marine Environmental Research, 2026)

New gastropod records for the Miocene Solimões Formation, Amazonas State, Brazil. Taxonomy, palaeobiogeography and palaeoenvironmental inferences - Lívia Isadora de Almeida Guimarães; Maria Inês Feijó Ramos; Nathália Silva Felix; Luiz Ricardo L. Simone (Palaeobiodiversity and Palaeoenvironments, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

Barcoding‐Inferred Biodiversity of Shallow‐Water Indo‐Pacific Demosponges - Dirk Erpenbeck; Adrian Galitz; Michael L. Berumen; Gabriele Büttner; Cécile Debitus; Moritz Dirnberger; Merrick Ekins; Kathryn Hall; Leonard Namuth; Sylvain Petek; Neda Rahnamae; Maggie M. Reddy; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Pacific is the world's largest marine biogeographic region. It is characterised by different degrees of connectivity among its subregions and harbours the majority of demosponge species currently known to science. Comparisons between regional sponge faunas have been undertaken in the past, mostly based on morphological species identification. The Sponge Barcoding Project, in tandem with regional DNA taxonomy campaigns, provides one of the largest DNA‐based taxonomic data collections from sponges of the Indo‐Pacific. Here, we utilise the barcoding data in the most extensive molecular biodiversity study of sponges to date, which reveals patterns of shallow‐water demosponge faunal connectivity, endemism and distribution in the Indo‐Pacific with a level of resolution unavailable in prior morphology‐based studies. Location Demosponge specimens in this study cover 13 marine provinces (MPs) of the Indo‐Pacific. Methods We classified demosponge barcodes from 1910 sponge samples into 701 molecular operational taxonomic units (MOTUs) using 28S rRNA. MOTU composition of the MPs was compared based on Jaccard and Sørenson dissimilarities and other biodiversity indices. Results Our data corroborated high endemism in MPs (up to 84.1% endemic MOTUs). Faunal overlaps are between the Red Sea and the Gulf, which displayed small connectivity with other MPs in the Western Indian Ocean. The Western Indian Ocean is a strong faunistic boundary to the Central Indo‐Pacific, to which the Polynesian sponge faunas were comparatively isolated as well. Main Conclusions Our data corroborate case studies on sponges that generally reject the presence of cosmopolitan or otherwise widespread sponge species, instead revealing high levels of regional endemism. This is consistent with similar observations and hypotheses in other marine invertebrates, and highlights the need for close regional monitoring to identify biodiversity changes. Connectivity among Indo‐Pacific MPs differs for demosponges in many aspects from that of other marine taxa, hypothetically due to their shorter pelagic larval phase.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Tundra Vegetation Community Type, Not Microclimate, Controls Asynchrony of Above‐ and Below‐Ground Phenology - Elise C. Gallois; Isla H. Myers‐Smith; Colleen M. Iversen; Verity G. Salmon; Laura L. Turner; Ruby An; Sarah C. Elmendorf; Courtney G. Collins; Madelaine J. R. Anderson; Amanda Young; Lisa Pilkinton; Gesche Blume‐Werry; et al. (Global Change Biology, 2025)
The below‐ground growing season often extends beyond the above‐ground growing season in tundra ecosystems and as the climate warms, shifts in growing seasons are expected. However, we do not yet know to what extent, when and where asynchrony in above‐ and below‐ground phenology occurs and whether variation is driven by local vegetation communities or spatial variation in microclimate. Here, we combined above‐ and below‐ground plant phenology metrics to compare the relative timings and magnitudes of leaf and fine‐root growth and senescence across microclimates and plant communities at five sites across the Arctic and alpine tundra biome. We observed asynchronous growth between above‐ and below‐ground plant tissue, with the below‐ground season extending up to 74% (~56 days) beyond the onset of above‐ground leaf senescence. Plant community type, rather than microclimate, was a key factor controlling the timing, productivity, and growth rates of fine roots, with graminoid roots exhibiting a distinct ‘pulse’ of growth later into the growing season than shrub roots. Our findings indicate the potential of vegetation change to influence below‐ground carbon storage as the climate warms and roots remain active in unfrozen soils for longer. Taken together, our findings of increased root growth in soils that remain thawed later into the growing season, in combination with ongoing tundra vegetation change including increased shrub and graminoid abundance, indicate increased below‐ground productivity and altered carbon cycling in the tundra biome.

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Declines in coastal macrozooplankton communities within a recent climate and ocean tipping point in the Tropical South Atlantic - Denise Fabiana de Moraes Costa Schwamborn; Catarina da Rocha Marcolin; Nathália Lins-Silva; Morgana Brito-Lolaia; Humberto L. Varona; Simone Maria de Albuquerque Lira; Alexandre Oliveira de Almeida; Ralf Schwamborn (Science of The Total Environment, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Detection and molecular characterization of a novel mitovirus associated with Passiflora edulis Sims - Yam Sousa Santos; Andreza Henrique Vidal; Emanuel Felipe Medeiros Abreu; Isadora Nogueira; Fábio Gelape Faleiro; Cristiano Castro Lacorte; Fernando L. Melo; Magnólia de Araújo Campos; Rafael Reis de Rezende; Tulio Morgan; Arvind Varsani; Poliane Alfenas-Zerbini; et al. (Archives of Virology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

In my own or in their own way? Evidence on the diffusion of renewable energy promotion instruments - R. Arbolino; R. Boffardi; M. Bonasia; L. De Simone; G. Ioppolo (Journal of Cleaner Production, 2024)

Biological invasions are a population‐level rather than a species‐level phenomenon - Phillip J. Haubrock; Ismael Soto; Danish A. Ahmed; Ali R. Ansari; Ali Serhan Tarkan; Irmak Kurtul; Rafael L. Macêdo; Adrián Lázaro‐Lobo; Mathieu Toutain; Ben Parker; Dagmara Błońska; Simone Guareschi; et al. (Global Change Biology, 2024)
Biological invasions pose a rapidly expanding threat to the persistence, functioning and service provisioning of ecosystems globally, and to socio‐economic interests. The stages of successful invasions are driven by the same mechanism that underlies adaptive changes across species in general—via natural selection on intraspecific variation in traits that influence survival and reproductive performance (i.e., fitness). Surprisingly, however, the rapid progress in the field of invasion science has resulted in a predominance of species‐level approaches (such as deny lists), often irrespective of natural selection theory, local adaptation and other population‐level processes that govern successful invasions. To address these issues, we analyse non‐native species dynamics at the population level by employing a database of European freshwater macroinvertebrate time series, to investigate spreading speed, abundance dynamics and impact assessments among populations. Our findings reveal substantial variability in spreading speed and abundance trends within and between macroinvertebrate species across biogeographic regions, indicating that levels of invasiveness and impact differ markedly. Discrepancies and inconsistencies among species‐level risk screenings and real population‐level data were also identified, highlighting the inherent challenges in accurately assessing population‐level effects through species‐level assessments. In recognition of the importance of population‐level assessments, we urge a shift in invasive species management frameworks, which should account for the dynamics of different populations and their environmental context. Adopting an adaptive, region‐specific and population‐focused approach is imperative, considering the diverse ecological contexts and varying degrees of susceptibility. Such an approach could improve and refine risk assessments while promoting mechanistic understandings of risks and impacts, thereby enabling the development of more effective conservation and management strategies.

Multiple island effects shape oceanographic processes and zooplankton size spectra off an oceanic archipelago in the Tropical Atlantic - Simone M.A. Lira; Ralf Schwamborn; Mauro de Melo Júnior; Humberto L. Varona; Syumara Queiroz; Doris Veleda; Alef J. Silva; Sigrid Neumann-Leitão; Moacyr Araujo; Catarina R. Marcolin (Journal of Marine Systems, 2024)

High Concentrations of Cannabidiol Induce Neurotoxicity in Neurosphere Culture System - Simone A. A. Romariz; Viviam Sanabria; Karina Ribeiro da Silva; Miguel L. Quintella; Bruna A. G. de Melo; Marimélia Porcionatto; Danilo Candido de Almeida; Beatriz M. Longo (Neurotoxicity Research, 2024)

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

Novel plant-associated genomoviruses from the Brazilian Cerrado biome - Flávia Milene B. Nery; Josiane G. Batista; Felipe Fochat. S. Melo; Simone G. Ribeiro; Leonardo S. Boiteux; Fernando L. Melo; Juliana Gabrielle I. Silva; Luciane de Nazaré A. Reis; Rita C. Pereira-Carvalho (Archives of Virology, 2023)

Bioherbicide potential of essential oils from plant species used in folk medicine and cuisine in the Amazon region - Joseila Maldaner; Fernanda Souza Silva; Darlisson de Alexandria Santos; Simone Yasue Simote Silva; Sebastião da Cruz Silva; Tatiane da Costa Lima; Selma L. Goulart; Bernardo Tomchinsky; Marilene Nunes Oliveira (South African Journal of Botany, 2023)

Study of fast in-line measurement techniques for water ice characterization - Carolina Cruz; Cláudio P. Fonte; Antonio De Simone; Felix K. Oppong; Will Jeatt; Thomas L. Rodgers (Journal of Food Engineering, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Could different aqueous humor and plasma cytokine profiles help differentiate between ocular sarcoidosis and ocular tuberculosis? - L. De Simone; M. Bonacini; R. Aldigeri; F. Alessandrello; V. Mastrofilippo; F. Gozzi; E. Bolletta; C. Adani; A. Zerbini; G. M. Cavallini; L. Fontana; C. Salvarani; et al. (Inflammation Research, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

Front lines of the COVID-19 pandemic: what is the effectiveness of using personal protective equipment in health service environments?—a systematic review - Cristiano Miranda de Araujo; Odilon Guariza-Filho; Flavio Magno Gonçalves; Isabela Bittencourt Basso; Angela Graciela Deliga Schroder; Bianca L. Cavalcante-Leão; Glória Cortz Ravazzi; Bianca Simone Zeigelboim; José Stechman-Neto; Rosane Sampaio Santos (International Archives of Occupational and Environmental Health, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Putative adverse outcome pathways for female reproductive disorders to improve testing and regulation of chemicals - Hanna K. L. Johansson; Pauliina Damdimopoulou; Majorie B. M. van Duursen; Julie Boberg; Delphine Franssen; Marijke de Cock; Kersti Jääger; Magdalena Wagner; Agne Velthut-Meikas; Yuling Xie; Lisa Connolly; Pauline Lelandais; et al. (Archives of Toxicology, 2020)
Modern living challenges female reproductive health. We are witnessing a rise in reproductive disorders and drop in birth rates across the world. The reasons for these manifestations are multifaceted and most likely include continuous exposure to an ever-increasing number of chemicals. The cause–effect relationships between chemical exposure and female reproductive disorders, however, have proven problematic to determine. This has made it difficult to assess the risks chemical exposures pose to a woman’s reproductive development and function. To address this challenge, this review uses the adverse outcome pathway (AOP) concept to summarize current knowledge about how chemical exposure can affect female reproductive health. We have a special focus on effects on the ovaries, since they are essential for lifelong reproductive health in women, being the source of both oocytes and several reproductive hormones, including sex steroids. The AOP framework is widely accepted as a new tool for toxicological safety assessment that enables better use of mechanistic knowledge for regulatory purposes. AOPs equip assessors and regulators with a pragmatic network of linear cause–effect relationships, enabling the use of a wider range of test method data in chemical risk assessment and regulation. Based on current knowledge, we propose ten putative AOPs relevant for female reproductive disorders that can be further elaborated and potentially be included in the AOPwiki. This effort is an important step towards better safeguarding the reproductive health of all girls and women.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Correction to: Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)

Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)
Stimulation of monocytes with microbial and non-microbial products, including oxidized low-density lipoprotein (oxLDL), induces a protracted pro-inflammatory, atherogenic phenotype sustained by metabolic and epigenetic reprogramming via a process called trained immunity . We investigated the intracellular metabolic mechanisms driving oxLDL-induced trained immunity in human primary monocytes and observed concomitant upregulation of glycolytic activity and oxygen consumption. In two separate cohorts of healthy volunteers, we assessed the impact of genetic variation in glycolytic genes on the training capacity of monocytes and found that variants mapped to glycolytic enzymes PFKFB3 and PFKP influenced trained immunity by oxLDL. Subsequent functional validation with inhibitors of glycolytic metabolism revealed dose-dependent inhibition of trained immunity in vitro. Furthermore, in vivo administration of the glucose metabolism modulator metformin abrogated the ability for human monocytes to mount a trained response to oxLDL. These findings underscore the importance of cellular metabolism for oxLDL-induced trained immunity and highlight potential immunomodulatory strategies for clinical management of atherosclerosis. Key messages Brief stimulation of monocytes to oxLDL induces a prolonged inflammatory phenotype. This is due to upregulation of glycolytic metabolism. Genetic variation in glycolytic genes modulates oxLDL-induced trained immunity. Pharmacological inhibition of glycolysis prevents trained immunity.

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Two epizootic Perkinsus spp. events in commercial oyster farms at Santa Catarina, Brazil - Ana C. Luz Cunha; Vitor de A. Pontinha; Maria Alcina M. de Castro; Simone Sühnel; Sthefanie C. Medeiros; Ângela M. Moura da Luz; Ricardo Harakava; Leonardo Tachibana; Danielle F. Mello; Naissa M. Danielli; Alcir L. Dafre; Aimê R. M. Magalhães; et al. (Journal of Fish Diseases, 2019)
Perkinsus spp. have been detected in various bivalve species from north‐east Brazil. Santa Catarina is a South Brasil state with the highest national oyster production. Considering the pathogenicity of some Perkinsus spp., a study was carried out to survey perkinsosis in two oyster species cultured in this State, the mangrove oyster Crassostrea gasar and the Pacific oyster Crassostrea gigas . Sampling involved eight sites along the state coast, and oyster sampling was collected during the period between January 2013 and December 2014. For the detection of Perkinsus , Ray's fluid thioglycollate medium (RFTM) and histology were used, and for the identification of the species, PCR and DNA sequencing were used. Perkinsus spp. was found by RFTM in C. gigas and C. gasar from São Francisco do Sul. This pathology was also detected in C. gasar from Balneário Barra do Sul both, by RFTM and histology. Perkinsus marinus was identified in C. gigas and C. gasar from São Francisco do Sul and Perkinsus beihaiensis in C. gasar from Balneário Barra do Sul. This is the first report of P. marinus in C. gigas from South America. Results of this preliminary study suggest that both oyster species tolerate the species of Perkinsus identified, without suffering heavy lesions.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Savanna turning into forest: concerted vegetation change at the ecotone between the Amazon and “Cerrado” biomes - Fábio Barbosa Passos; Beatriz Schwantes Marimon; Oliver L. Phillips; Paulo Sérgio Morandi; Eder Carvalho das Neves; Fernando Elias; Simone Matias Reis; Bianca de Oliveira; Ted R. Feldpausch; Ben Hur Marimon Júnior (Brazilian Journal of Botany, 2018)

Correction to: Cryptosporidium Spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Cryptosporidium spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Biological aspects of Bemisia tabaci biotype B and the chemical causes of resistance in soybean genotypes - Simone S. Vieira; André L. Lourenção; José P. da Graça; Tatiani Janegitz; Mariana C. Salvador; Maria Cristina N. de Oliveira; Clara Beatriz Hoffmann-Campo (Arthropod-Plant Interactions, 2016)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

Double-phase culture system for large scale production of pineapple - Jonny E. Scherwinski-Pereira; Elequisandra da C. Araruna Lima; Tatiane L. da Silva; Antonio G. Gomes Mesquita; Simone de A. Maciel; Frederico H. da Silva Costa (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Solid Dispersions of Imidazolidinedione by PEG and PVP Polymers with Potential Antischistosomal Activities - Francimary L. Guedes; Boaz G. de Oliveira; Marcelo Z. Hernandes; Carlos A. De Simone; Francisco J. B. Veiga; Maria do Carmo A. de Lima; Ivan R. Pitta; Suely L. Galdino; Pedro José Rolim Neto (AAPS PharmSciTech, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Karyotypic and molecular polymorphisms in Ctenomys torquatus (Rodentia: Ctenomyidae): taxonomic considerations - Fabiano A. Fernandes; Gislene L. Gonçalves; Simone S. F. Ximenes; Thales R. O. de Freitas (Genetica, 2009)

Differentiation in DNA fingerprinting among species of the genus Acer L. in Campania (Italy) - C. Guarino; S. Santoro; L. De Simone; G. Cipriani; R. Testolin (Plant Biosystems, 2008)

Identification and characterization of proteases from skin mucus of tambacu, a Neotropical hybrid fish - C. M. C. Salles; P. Gagliano; S. A. T. Leitão; J. B. Salles; H. L. M. Guedes; V. P. F. Cassano; S. Giovanni De-Simone (Fish Physiology and Biochemistry, 2007)

Visual feedback reduces bimanual coupling of movement amplitudes, but not of directions - Simone Cardoso de Oliveira; Sbastien Barthlmy (Experimental Brain Research, 2005)